2020
DOI: 10.1002/hed.26083
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of XRCC‐1 Arg194Trp polymorphism as bio‐predictor for clinical outcome in locally advanced laryngeal cancer undergoing cisplatin‐based chemoradiation

Abstract: Background: To determine X-ray repair cross-complementing 1 gene (XRCC-1) Arg194Trp polymorphism as bio-predictor for clinical outcome in advanced laryngeal squamous cell carcinoma undergoing cisplatin-based chemoradiation (CRT). Methods: A total of 150 patients were enrolled in this prospective study.XRCC-1 Arg194Trp genotyping categorized patients as wild (C/C) and polymorphic (C/T or T/T). The primary endpoint was to assess acute radiationinduced toxicity (ARIT).Results: A significant correlation of skin (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Several studies reported the correlation of genetic variants and skin reaction. However, these studies mainly investigated breast cancer patients using candidate gene association study strategies [24][25][26][27][28]. Polymorphisms of XRCC1 were the most widely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported the correlation of genetic variants and skin reaction. However, these studies mainly investigated breast cancer patients using candidate gene association study strategies [24][25][26][27][28]. Polymorphisms of XRCC1 were the most widely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Variants detected in genes involved in DNA damage response or DNA repair are associated with acute toxicities (mucositis and dermatitis) related to RT. 18 published studies evaluated the association of variants in DNA damage and DNA repair with RT-induced acute toxicities, 6 out of the 18 studies focused on variants in X-Ray Repair Cross Complementing 1 gene (XRCC1) as a DNA repair gene highly associated with radiotherapy toxicity 61, 63, 74, 75, 98 . Other variants in DNA damage and repair genes; XRCC2, XPD, ERCC1, ZNF24, NBN, Ku70, ATM, CHEK1, RAD51C, ERCC2, PMS1, MLH1 were associated with RT-acute toxicities, these results matched our study of the potential mechanisms of inflammatory pain induced by RT 22 .…”
Section: Discussionmentioning
confidence: 99%
“…(Figure 3, Table 5). 61,63,74,75,98 . Other variants in DNA damage and repair genes; XRCC2, XPD, ERCC1, ZNF24, NBN, Ku70, ATM, CHEK1, RAD51C, ERCC2, PMS1, MLH1 were associated with RTacute toxicities, these results matched our study of the potential mechanisms of inflammatory pain induced by RT 22 .…”
Section: -Variants Associated With Mixed Types Of Radiotherapy Induce...mentioning
confidence: 99%
“…Studies have investigated the association between XRCC1 Arg399Gln/XRCC1 Arg194Trp polymorphisms and HNSCC risk [17][18][19][20][21][22][23]. However, these results were contradictory.…”
Section: Discussionmentioning
confidence: 99%